2021
DOI: 10.1177/20595131211023388
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of the recurrence of surgically removed previous caesarean skin scars at caesarean section: A retrospective cohort study

Abstract: Background: Caesarean skin scars (CSS; hypertrophic scars and keloids) are very stressful for women and treatment strategies vary. However, there is a lack of knowledge about the outcome of surgical excision of CSS during caesarean section (CS). The study aims to determine the rate of recurrence and risk factors of recurrence for surgically removed CSS. Method: This is a retrospective cohort study that used STROBE guidelines. Pfannenstiel incisions of 145 patients were evaluated. Patients were divided into two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
1
0
Order By: Relevance
“…With respect to risk factors for hypertrophic scarring after C/S, Bagli et al 25 reported that emergency C/S was a risk factor for recurrent hypertrophic scarring in their retrospective study of 145 patients with repeat C/S, but the difference was not statistically significant. In the present study, emergency C/S was not a risk factor, and neither was HDP, obesity, or superficial SSI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With respect to risk factors for hypertrophic scarring after C/S, Bagli et al 25 reported that emergency C/S was a risk factor for recurrent hypertrophic scarring in their retrospective study of 145 patients with repeat C/S, but the difference was not statistically significant. In the present study, emergency C/S was not a risk factor, and neither was HDP, obesity, or superficial SSI.…”
Section: Discussionmentioning
confidence: 99%
“…19 In addition, the Japan Scar Workshop Scar Scale 2015 (JSS) 20,21 was developed in Japan as a more reproducible evaluation method with specific photographic examples and is used in clinical practice and research. [22][23][24][25] As evaluation methods have been refined, higher-quality evidence is required.…”
Section: Original Investigationmentioning
confidence: 99%
“…Finally, the esthetic issues after incision healing need to be considered. The Pfannenstiel incision is known as a "bikini incision" because it can be hidden beneath underwear; however, the resulting scar may create certain esthetic issues for female patients 31 . As the scar from our incision is hidden by the pubic hair (Fig.…”
Section: Discussionmentioning
confidence: 99%